THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF TEAM ASSISTED INDIVIDUALIZATION ON STUDENTS’ MATHEMATICS LEARNING OUTCOMES IN GRADE VIII - Lailatul Khoiriyah; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Teacher-centered learning and lack of learning media make the students pay less attention to explaining what the teacher gives, affecting the students learning results. The use of the cooperative learning model of Team Assisted Individualization (TAI) is expected to improve students learning results. The purpose of this study is to determine whether or not there are differences in mathematics learning outcomes between students using TAI type of cooperative learning model with direct learning model and to find out whether the TAI type of cooperative learning model is more effective than the direct learning model to the results of class VIII even semester of Muhammadiyah Junior High School (SMP Muhammadiyah) 1 Minggir Sleman District Academic Year of 2016/2017. This study's population was 237 students of class VIII at SMP Muhammadiyah 1 Minggir Academic Year of 2016/2017, consisting of seven classes. Samples were taken two classes using a random sampling technique that is by drawing. Derived VIII G as the experiment class and VIII F as the control class. Method of data collection using the student's initial ability documentation and test methods. The instrument of this research is the test of mathematics learning results in the form of multiple choice. Analysis of data used is test prerequisite analysis consisting of a normality test and homogeneity test. The hypothesis test used is a paired t-test and a one-sample t-test. The results in the significant level of 5% and db = 66 show that : (1) there are differences in students' mathematics learning outcomes using TAI and mathematics learning outcomes of students who use the direct learning. The value of tcount = 3.3587 evidenced this and ttable = 1,9949 so that tcount > ttable means that rejecting H0 and accept H1. (2) Mathematic learning of students who used cooperative learning model type of TAI was more effective than students who used direct learning on mathematics learning outcomes. The value of tcount = 3.3587 evidenced this and ttable = 1,6672 so that tcount > ttable means that rejecting H0 and accept H1.